(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
An integrated fertilizer experiment was conducted on the spinach plant at the net house of Soil, Water and Environment department under University of Dhaka during the rabi season using pot culture. The intention of the study was to evaluate the integrated effect of vermicompost, NPK fertilizers, Cd and Pb on soil properties, spinach growth, yield and concentration of nutrients. The trial was carried out in a Completely Randomized Design (CRD) followed by two replications, having twelve treatments, including control. The maximum growth and yield contributing characteristics of spinach plant viz. plant height (23.10 cm), leaf area (61.13 cm2 plant-1), length of leaf (10.85 cm plant-1), no. of leaf (10 plant-1), yield of fresh (10.92g plant-1) and dry materials (1.05g plant-1) found in T12 (vermicompost 5 ton ha-1 + N25P8K10 kg ha-1 + Pb4 kg ha-1). All the growth and yield parameters observed lowest with the sole Cd application and the performance of sole Pb also showed reducing trends compared to other integrated treatments. The highest achievements of macro elements N (0.0798%), P (0.0027%), K (0.0068%) and S (0.0084%) of post-harvest soil with the treated pot in T12 over the control. Mineral nutrients of leaves (N-2.29%, P-1.30% and K-8.24%) were found highest in the same T12. It may be concluded that the maximum production of spinach, sustain the soil productivity and achieve the high nutritional value of the leaf in the treatment T12 (vermicompost 5 ton ha-1 + N25P8K10 kg ha-1 + Pb4 kg ha-1) recommended for its cultivation. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 13-24